2009
DOI: 10.1007/s10919-008-0064-8
|View full text |Cite
|
Sign up to set email alerts
|

On the Correspondence Between Physiological and Nonverbal Responses: Nonverbal Behavior Accompanying Challenge and Threat

Abstract: Little is known regarding the covariance between physiological and nonverbal responses to ''stressful'' situations. We argue that physiological markers are especially likely to be accompanied by psychologically-meaningful nonverbal behavior. Within ''stressful'' motivated performance situations, complex patterns of cardiovascular (CV) reactivity mark challenge and threat motivational states relevant to confidence. We expected the CV challenge and threat markers to be distinguished on the basis of facial and vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 24 publications
1
30
0
1
Order By: Relevance
“…Several studies have supported this prediction (O'Connor et al, 2010;Weisbuch, Seery, Ambady, & Blascovich, 2009). For instance, Mendes et al (2007) found that, compared to a threat state, a challenge state resulted in more effective movements during an interaction task, including less freezing, avoidance posture, and more smiling.…”
Section: Possible Underlying Mechanismsmentioning
confidence: 86%
“…Several studies have supported this prediction (O'Connor et al, 2010;Weisbuch, Seery, Ambady, & Blascovich, 2009). For instance, Mendes et al (2007) found that, compared to a threat state, a challenge state resulted in more effective movements during an interaction task, including less freezing, avoidance posture, and more smiling.…”
Section: Possible Underlying Mechanismsmentioning
confidence: 86%
“…Higher scores on self-efficacy for individuals in a threat state may reflect an attempt to mask an underlying lack of self-efficacy. Indeed, individuals who exhibited cardiovascular responses indicative of threat during a social interaction with a stranger sounded less confident, but looked more confident (Weisbuch, Seery, Ambady, & Blascovich, 2009). To explain, participants who were threatened in a social interaction attempted to mask an underlying lack of confidence by controlling their facial display which CHALLENGE AND THREAT STATES 18 is relatively controllable compared to vocal confidence.…”
Section: Discussionmentioning
confidence: 99%
“…We calculated a threat-challenge index by converting CO and TPR reactivity scores into z-scores, and then subtracting TPR from CO, which means that higher values on the resulting index indicate a stronger challenge motivational state whereas lower values indicate a stronger threat motivational state (Blascovich et al, 2004;Kassam, Koslov, & Mendes, 2009;Mendes et al, 2007;Seery et al, 2009;Weisbuch, Seery, Ambady, & Blascovich, 2009). In line with predictions, participants in the high power condition were relatively more challenged (M = .69) than participants in the low power condition (M = −.44), who were relatively more threatened, F(1,43) = 4.59, p =.038 (see Fig.…”
Section: Cardiovascular Reactivitymentioning
confidence: 99%